Customary Rights and Freshwater Ecology in Pluralistic Societies on the Monsoonal Island of Sumba (Eastern Indonesia) - Fowler, Cynthia T. (Frontiers in Environmental Science, 2022)
This article evaluates the ways water is made and unmade on Sumba Island when subjected to tensions between Indigenous and off-island political ecologies. Located in the eastern Indian Ocean, Sumba has a semi-arid, monsoonal climate with an uplifted coral reef geological structure where a spatially and temporally dynamic hydrological system shapes people’s access to freshwater. Customary adat societies on the island have histories of struggling to maintain the integrity of their own political ecologies, further increasing the precarity of their access to freshwater. The topic of the research reported on in this paper was determined through collaboration with members of the Kodi community in western Sumba who urged the author to study the problem of water. This article highlights ongoing threats to the further degradation of local societies’ rights to control their customary territories and freshwater within them by summarizing the phenomena of water grabbing in Indonesia. Zooming in on three projects that manifest as water grabs, this article finds, respectively, that water grabbing occurs under the guise of forest protection and production, behind the veil of philanthropy, and for economic development with military backing. In all three cases, water grabs take place in the context of a decentralizing nation-state where the ways adat is understood and the ways laws regarding it have been interpreted and enacted have changed through time and have varied between communities, partly in relation to the societies’ proximity to centers of colonial and postcolonial power as well as the development of activities in their territories. On Sumba the content of adat and relationships among distinct adat societies evolves on a bioculturally diverse island that is home to numerous Indigenous ethnolinguistic communities. Consequently, people’s responses to interventions into their political ecologies vary. More broadly, the context for this study is the intersections of water grabbing and social change during the Reformasi, the post-Suharto era of decentralization in Indonesia.